Prophetic activism : progressive religious justice movements in contemporary America - Slessarev-Jamir, Helene (Religion and social transformation., 2011)
While the links between conservative Christians and politics have been drawn strongly in recent years, coming to embody what many think of as religious activism, the profoundly religious nature of community organizing and other more left-leaning justice work has been largely overlooked. Prophetic Activism is the first broad comparative examination of progressive religious activism in the United States. Set up as a counter-narrative to religious conservatism, the book offers readers a deeper understanding of the richness and diversity of contemporary religious activism. Helene Slessarev-Jamir o.